Penerapan Endorphin Massage Sebagai Terapi Komplementer Dalam Menurunkan Tingkat Dysmenorhea Pada Remaja Putri - Fatma Jama; Andi Tenri Abeng; Yusrah Taqiyah; Latifa Rahmawati Bauw; Indriyani Sahalani (Borneo Community Health Service Journal, 2025)
Dysmenorrhoea is often experienced by young women, this can disturb feelings of comfort and interfere with daily activities, generally it is not dangerous but must be treated immediately. Endorphin Massage is a non-pharmacological therapy that can reduce the level of pain in young women who experience dysmenorrhoea. This endorphin massage can stimulate the body to release endorphin compounds which are natural pain relievers and can create a feeling of comfort through light touches on the surface of the skin. Based on field studies, it was found that Endorphin Massage had not been implemented in schools, especially at UPT.SMKN 6 Takalar. The aim of this activity is to increase the knowledge and skills of Young Women in dealing with Dysmenorrhea after being given Endorphin Massage Counseling and Training. The methods used in this activity are lectures, discussions and demonstrations of Endorphin Massage for young women. Before the intervention is carried out, first assess the participant's level of knowledge and skills by means of a pre-test and post-test. The results of this Community Service activity were that after conducting education and Endorphin Massage simulations for young women, the knowledge and skills of young women increased rapidly from 6% to 100%. It is hoped that in this activity young women can treat dysmenorrhea by using complementary therapy as an alternative treatment.